Hubungan Kepatuhan Penggunaan Antidiabetik Oral Pada Pasien Diabetes Mellitus Tipe II Terhadap Kualitas Hidup Pasien Di Rumah Sakit Harapan Bunda - Dewi, Fransiska Ariana; Nurkhalika, Rachmi; Saputri, Gusti Ayu Rai (Peneliti.net, 2024)
Type 2 Diabetes Mellitus (DM) is a serious and chronic disease characterized by high blood glucose levels. The successful management of DM is influenced by several factors, including patient adherence in taking medication, which in turn can reduce morbidity and mortality and improve the patient's quality of life. The purpose of this study was to determine the relationship between adherence to the use of oral antidiabetics in patients with type 2 diabetes mellitus at Harapan Bunda Hospital, Lampung Tengah. This research method is a non-experimental study with a cross-sectional research design. The results of the study obtained a compliance p-value of 0.001 (<0.05) which means there is a strong comelation between medical adhenence and patients quality of life.